2018
DOI: 10.1186/s13287-018-1030-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficiency of bone marrow mesenchymal stem cell implantation for osteonecrosis of the femoral head: a matched pair control study with simple core decompression

Abstract: BackgroundTo date, several trials have reported the use of mesenchymal stem cell (MSC) implantation for osteonecrosis of the femoral head (ONFH). However, the clinical outcomes have not been conclusive. This study compared the clinical and radiological results of bone marrow mesenchymal stem cell (BMMSC) implantation with traditional simple core decompression (CD) using a matched pair case–control design.MethodsWe retrospectively reviewed 100 patients with ONFH (106 hips) who had been treated by CD alone (50 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
83
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 35 publications
(45 reference statements)
0
83
0
2
Order By: Relevance
“…The early step of bone formation involves the migration of mesenchymal stem cells (MSC), which undergo proliferation and differentiation along the osteoblastic lineage. Indeed, MSC implantation has emerged as a promising strategy for promoting bone regeneration in several clinical conditions, including delayed unions and non-unions, critical-sized bone defects, periprosthetic osteolysis, osteonecrosis, and inflammatory bone disorders [6][7][8][9][10]. The benefits of MSC therapy are mainly attributed to paracrine effects via soluble factors, exerting both immunoregulatory and regenerative actions [11].…”
Section: Introductionmentioning
confidence: 99%
“…The early step of bone formation involves the migration of mesenchymal stem cells (MSC), which undergo proliferation and differentiation along the osteoblastic lineage. Indeed, MSC implantation has emerged as a promising strategy for promoting bone regeneration in several clinical conditions, including delayed unions and non-unions, critical-sized bone defects, periprosthetic osteolysis, osteonecrosis, and inflammatory bone disorders [6][7][8][9][10]. The benefits of MSC therapy are mainly attributed to paracrine effects via soluble factors, exerting both immunoregulatory and regenerative actions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Sugaya's team confirmed the efficacy of local BMSC transplantation in the treatment of femoral head necrosis through animal experiments; they showed that BMSCs in the necrotic area can survive, proliferate, differentiate into bone, and promote repair [19,20]. However, stem cell therapy for osteonecrosis has not shown sufficient repair outcomes in clinical application [7]. Wojciech Pepke compared the individual efficacy of bone marrow cell implantation and core decompression in the treatment of early-stage ONFH and found no significant difference between treatments in the postoperative change in necrotic area [11].…”
Section: Discussionmentioning
confidence: 99%
“…Femoral head necrosis is a disease involving the activity of local stem cells in the femoral head [6]. In ONFH patients, the number and viability of mesenchymal stem cells (MSCs) in the femoral head were found to be decreased [7]. Therefore, stem cell implantation is a potential treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, the total number of procedures performed for ONFH is doubled [2]. Sadly, the longterm results of hip preserving procedures are not favourable, so the surgical techniques have to evolve in order to achieve better results [3]. The authors reported mid-term follow-up of a series of muscle pedicle graft treatment for ONFH.…”
mentioning
confidence: 99%
“…The technique is encouraging and I would like to congratulate authors for their study, theoretically, procedures that provide a blood supply for necrotic area could be more effective than conventional CD or even structural allografts. Conversion to total hip arthroplasty (THA) and any progress or changes in staging were considered as outcome measurement in this study which are used repeatedly in same studies [3][4][5]. The authors reported success rate of 87.5% because at final followup, only three out of 24 hips have been converted to THA; I do not agree with this result.…”
mentioning
confidence: 99%